Ivermecatin induces cytotoxic effects in SUP-B15 cell line - Siregar, Olga Rasiyanti; Wahyuni, Arlinda Sari; Pasaribu, Ayodhia Pitaloka; Edianto, Deri; Ugrasena, I Dewa Gede; Amelia, Rina; Lubis, Inke Nadia Diniyanti; Rusda, Muhammad (The Turkish Journal of Pediatrics, 2025)
Background. Glucocorticoids remain the primary treatment for acute lymphoblastic leukemia (ALL) in children. However, glucocorticoid-resistant ALL exhibits increased mortality rates. To overcome resistance and improve management strategies, alternative therapeutic agents are required. Ivermectin (IVM), widely used as an anthelmintic agent, has been reported to possess anticancer properties through various mechanisms. These properties suggest IVM as a potential alternative treatment for ALL. This study aims to evaluate the role of IVM in inducing cytotoxic effects in the ALL cell line SUP-B15.Methods. The ALL cell line SUP-B15 was examined following treatment with IVM at concentrations of 5, 10, and 20 μM. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to assess cytotoxic effects of IVM, including measurements of optical density, cell inhibition, and cell viability.Results. IVM demonstrated inhibitory effects on SUP-B15 cells starting at a low dose of 5 μM. The half maximal inhibitory concentration (IC50) of IVM was 5 µM, showing an inhibitory effect of 54.18 ± 0.03% (95% confidence interval: 54.11-54.25%; p < 0.001). Treatment with 10 μM IVM demonstrated the most significant inhibitory effect (59.05 ± 0.1%) and the lowest cell viability (40.95 ± 0.01%).Conclusions. IVM holds potential as a promising alternative therapeutic agent for the treatment of ALL.
Keywords: acute lymphoblastic leukemia; apoptosis; ivermectin; glucocorticoid resistance